A darker side of knowledge transfer following international acquisitions. (23rd April 2015) - Reus, Taco H.; Lamont, Bruce T.; Ellis, Kimberly M.
Abstract : We consider a knowledge flow that dominates the international acquisition context but can actually harm foreign acquired firms' performance: non–location‐specific knowledge transfer from acquirers to acquired firms (N‐LSKT). Considering its behavioral consequences, we argue that such knowledge transfer often may destabilize existing power structures in foreign acquired firms prompting conflict and power struggles, and as a result negatively affects their performance. We find support for this adverse knowledge transfer effect. Only at very high levels of N‐LSKT, when acquirers are likely to extend their own capabilities and associated power structures more completely, do the performance effects improve. Further, predeal success of acquirers and post‐deal functional integration amplify, while acquirers' strategic control over the acquired firm alleviates the generally negative effects of N‐LSKT . Copyright © 2015 John Wiley & Sons, Ltd.